Occurrence and ethnomycological notes on Phallus indusiatus (Phallaceae, Basidiomycota) in the Reserva Extrativista Tapajós-Arapiuns, Pará, Brazil - Ferreira Santana, Marcos Diones; Lopes Costa, Ana Daiane; Costa Gomes, Emeli Susane; Santos Guimarães, Luciana Edilena (Instituto de Ecología, A.C., 2019)
Background and Aims: Studies about Phallus (Phallaceae, Basidiomycota) in the Amazon are scarce, considering the knowledge gaps of the taxon. In the Reserva Extrativista Tapajós-Arapiuns, state of Pará, Brazil, the occurrence of P. indusiatus, and their local names were not known. Hence, the first record of this species in the area is presented, including two local names used by riparians of that locality, and a popular taxonomic system to recognize the macroscopic fungi.Methods: During May 2016, expeditions were carried out in Vila Franca and Maripá, traditional communities of the Reserva Extrativista (RESEX) Tapajós-Arapiuns, in the west of the state of Pará, as well as open interviews with the riparians of these communities.Key results: In both communities, the prefix Urupê was used to designate macroscopic fungi. For the recognition of P. indusiatus among other fungi, the riparians of each community attributed a second term derived to the prefix, being identified as Urupê-tajá-de-cobra in Vila Franca and Urupê-véu-de-noiva in Maripá.Conclusions: The popular taxonomic system of the riparians is useful in the study of the diversity of fungi and its conservation is necessary mainly in areas witch are little or not yet studied. The ethnoknowledge about Phallus constitutes important information in light of the existing knowledge gaps on the taxon and broadens the horizons to further ethnomycological studies in Amazon.